Capacitação da equipe de clínica médica quanto às atualizações do manejo agudo hospitalar de fibrilação atrial de alta resposta ventricular - Victor Souza Nobre; Marilia Mendes de Saboya; Felipe de Araújo Lucena; Camila Amora Santos Albuquerque D’Alva; Natália Marinho Porto Lima; Luiza Targino Studart; José de Ribamar Barroso Jucá Neto (Revista ft, 2026)
Atrial fibrillation with rapid ventricular response is a common condition in the hospital setting and requires prompt recognition, assessment of hemodynamic stability, and evidence-based therapeutic decision-making. Given the variability in clinical management and the need for professional updating, this study aims to train the Internal Medicine medical team on current recommendations for the acute hospital management of atrial fibrillation with rapid ventricular response, with the goal of standardizing clinical practices, strengthening clinical decision-making, and improving patient safety. This is an educational intervention project directed at on-duty and daytime physicians at a high-complexity tertiary hospital in Fortaleza, Ceará, from October to November 2026. The intervention will be conducted through an interactive in-person lecture based on clinical cases, addressing arrhythmia recognition, identification of hemodynamic instability, initial management, and the main therapeutic options supported by current clinical guidelines. The internal educational assessment will be conducted through participant feedback regarding the relevance of the content and its applicability to clinical practice. The intervention is expected to promote greater knowledge and confidence in the management of atrial fibrillation with rapid ventricular response, as well as to contribute to the standardization of clinical practices and the ongoing professional development of the medical team. It is concluded that structured educational interventions may constitute a relevant strategy for improving the hospital management of this arrhythmia and strengthening evidence-based clinical practices.